Penerapan Bahasa Jurnalistik Radio pada Berita Ekonomi dalam Program “Halo Bharabas” di Radio Bharabas FM Pekanbaru - Monika, Dinda; Wahidar, Tutut Ismi (Indonesian Social Science Review, 2024)
Using language in journalism is very important. This research aims to find out how journalistic language is applied in the "Halo Bharabas" program on Radio Bharabas FM Pekanbaru. On this research, the researcher used the concept of radio journalistic language by Harley Prayudha. The researcher used descriptive qualitative method. The subject of this research is Bharabas FM Radio and the object is how is the application of radio journalistic language in economics news. The techniques of data collections are observing, interviewing and documenting. The research located in Kali Putih Street number 3, Pekanbaru City, Riau. The sources of the data are collected from President Director of Bharabas radio, script editor and news manager, who is also the radio announcer on Radio Bharabas. From the data, the researcher found the application of radio journalistic language in economics news in Halo Bharabas program based on Harley Prayudha concept, there are five points among twelve of characteristics that applicated in Bharabas FM pekanbaru program.Those are, limited vocabulary, the using of abbreviation is still could be found, simple sentences are not implementing well, have not used the transition words and supported by the voice prompt still happening repeatedly.  And the last is there are structural of negative sentences. The most incompatibility that frequently found are the utilization of abbreviation. The researcher collected thirteen news and only found a single of them that do not contain the abbreviation. For instance, on the second news found that there are seven abbreviation such as, HET, SPHP, PIBC, Satgas, Bulog, Polres and Polsek. Penggunaan bahasa dalam jurnalistik sangat penting. Penelitian ini bertujuan untuk mengetahui bagaimana penerapan bahasa jurnalistik dalam program “Halo Bharabas” di Radio Bharabas FM Pekanbaru. Penelitian ini menggunakan konsep bahasa jurnalistik radio menurut Harley Prayudha. Pendekatan yang digunakan ialah kualitatif dengan metode penelitian yakni deskriptif kualitatif. Subjek dalam penelitian ini ialah Radio Bharabas FM, dan objekya ialah penerapan bahasa jurnalistik radio pada program berita ekonomi. Teknik pengumpulan data yang digunakan yakni observasi, wawancara, dan dokumentasi. Lokasi penelitian berada di kantor Radio Bharabas yang beralamat di Jalan Kali Putih No 3, Kota Pekanbaru, Riau. Informan dalam penelitian ini ialah direktur utama Radio Bharabas, Penata naskah sekaligus manager pemberitaan Radio Bharabas, dan penyiar Radio Bharabas.Hasil penelitian ini menunjukkan bahwa penerapan bahasa jurnalistik radio pada berita ekonomi dalam program “Halo Bharabas” di Radio Bharabas FM Pekanbaru masih terdapat lima dari dua belas karakteristik menurut Harley Prayudha yang belum diterapkan dengan baik. Lima karakteristik tersebut ialah kosata kata terbatas, masih menggunakan singkatan-singkatan, belum mengunakan kalimat yang sederhana, belum menggunakan kata transisi dan petunjuk suara lebih sering, dan masih terdapat susunan kalimat negatif. Ketidaksesuaian yang paling sering ditemukan yakni dalam penggunaan singkatan-singkatan, dari tiga belas berita hanya satu berita yang tidak terdapat penggunaan singkatan. Contohnya pada berita dua dimana ditemukan tujuh singkatan seperti HET, SPHP, PIBC, Satgas, Bulog, Polres, dan Polsek.